Effects of Family Responsibilities, Gender, and Career Identity Salience on Performance Outcomes - Lobel, Sharon A.; Clair, Lynda St. (Academy of Management Journal, 1992)
Predictions based on the human capital, gender discrimination, and social identity theories were tested. Individuals with salient career identities were willing to expend extra effort at work and received higher merit increases than people with salient family identities. When we controlled identity salience, neither extensive family responsibilities nor female gender adversely affected merit increases. Family-oriented women with preschoolers received higher merit increases than family-oriented men with preschoolers, but career-oriented men with preschoolers received higher merit increases than career-oriented women with preschoolers.